A generalized driving risk assessment on high-speed highways using field theory - Joo, Yang Jun; Kim, Eui Jin; Kim, Dong Kyu; Park, Peter Y. (Analytic Methods in Accident Research, 2023)
This study presents a new safety measure derived from field theory. It evaluates the risk arising from the various concurrent conflicts within a platoon that can occur on high-speed highway driving situations, such as car-following, yielding, and lane changing. We defined the risk field as a finite scalar field produced by traveling vehicles on the road, and we defined the conflict field as the overlapping risk field between any vehicles in proximity on the roadway. The study used a probabilistic trajectory prediction model to construct risk fields and an approximation method to reduce the computational time for real-time applications. To demonstrate the applicability of the proposed new measure, we applied it to real-world trajectory data (NGSIM data from US Highway 101). We compared the results with three traditional conflict-based safety measures: post-encroachment time (PET), modified time-to-collision (MTTC), and deceleration rate to avoid a crash (DRAC). The new measure produced seamless and continuous risk estimations even during time windows when the other measures could not estimate the risk between vehicles. This is a major advantage over traditional measures. The study also developed visual displays of the estimated conflict fields to provide safety analysts with an intuitive and fast understanding of the results of the safety assessments made using the conflict field measure. We conclude that the proposed new safety measure provides a robust, reliable, and improved assessment of the risk involved in expected future mixed-traffic environments that involve both human-driven vehicles and automated vehicles in the future.
Keywords: Driving risk assessment; Driving risk visualization; Field theory; Probabilistic trajectory prediction; Probabilistics; Risk visualization; Risks assessments; Traffic conflict measure; Traffic conflicts; Trajectory prediction; Driving risk assessment; Driving risk visualization; Field theory; Probabilistic trajectory prediction; Traffic conflict measures